Evaluation of the Effectiveness of Olive Leaf Extract as a Natural Insecticide for the Control of Olive Psyllid (Euphyllura olivina) - Mustafa Al-Hadi Al-Saadi; Abdullah Abdulsalam Al-Hajin; Mohamed Dulayoum (African Journal of Advanced Pure and Applied Sciences, 2026)
This study aimed to evaluate the insecticidal effectiveness of olive leaf extracts (local Enduri cultivar) against the olive psyllid (Euphyllura olivina) in Libya. The research investigated two extraction methods: Aqueous Infusion and Organic Solvent (Methanolic) Extract. Experiments were conducted under laboratory and field conditions using three concentrations (15%, 20%, and 25%), compared with a conventional chemical insecticide and a control group. The results demonstrated the superiority of the Methanolic Extract, achieving the highest mortality rate of 87% at the 25% concentration, followed by the Aqueous Extract at 80% after 72 hours of treatment. Field trials further confirmed the extracts’ efficiency in significantly reducing pest population density. The study concludes that olive leaf extracts, particularly the methanolic one, serve as a safe and effective bio-alternative to synthetic pesticides, supporting Integrated Pest Management (IPM) strategies and sustainable agriculture.